2019
DOI: 10.3390/w11020231
|View full text |Cite
|
Sign up to set email alerts
|

Examining Water Security in the Challenging Environment in Togo, West Africa

Abstract: Water shortages across the globe have increased due to climate change among other factors with negative impacts expected at the river basin level. Anticipating these impacts will help experts act in a timely manner to avoid a future water crisis. As part of addressing the future water shortage impacts on the Togolese community, this paper assessed water security in the context of the global environmental change in the Oti River Basin taking Oti Nord sub-basin (ONSB) as a case study. Key informants' interviews … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…There are few reports on waterborne disease contamination related to flooding events in Togo. Therefore, a study conducted for examining water security in the challenging environment in Togo revealed inadequacies in water quality, and the absence of de-centralized water management structures [ 39 ]. As presented by the authors, this situation of water could render difficult interventions during flooding periods in this area.…”
Section: Discussionmentioning
confidence: 99%
“…There are few reports on waterborne disease contamination related to flooding events in Togo. Therefore, a study conducted for examining water security in the challenging environment in Togo revealed inadequacies in water quality, and the absence of de-centralized water management structures [ 39 ]. As presented by the authors, this situation of water could render difficult interventions during flooding periods in this area.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, the journal Water (bottom left quadrant) publishes most frequently on Topics 16-Water Security and Supply and 3-Water Research, Governance, and Development. Recent publications include topics on water scarcity and inefficient water usage in the United States [61], the effects of constitutionalizing the human right to water [27], water governance and policy in India [62], water security challenges in Togo [63]. Across each of the top four journals, the multidisciplinary nature of topics is quite apparent which speaks to the importance of engagement with a wide selection of academic outlets.…”
Section: Main Topics Across Journalsmentioning
confidence: 99%
“…The new tariff structure aims to reflect the growing cost of producing water and contribute to fund US$ 440 million investment into the country's water and wastewater infrastructure over the next three years (Nyiransabimana et al 2019). The continent's second-highest tariff increase since 2018 at 19.0% was found in Lomé (Togo), where the West African country updated its tariff structure (Yomo et al 2019) by adding a monthly fixed fee of US$ 1.25 for meter rental. Mbabane (eSwatini) is also undertaking a three-year tariff adjustment plan resulting in a 13.6% increase in the combined water and wastewater bill since 2018.…”
Section: Sub-saharan Africamentioning
confidence: 99%